In Situ Modification of a Delafossite-Type PdCoO2 Bulk Single Crystal for Reversible Hydrogen Sorption and Fast Hydrogen Evolution - Li, Guowei; Khim, Seunghyun; Chang, Celesta S.; Fu, Chenguang; Nandi, Nabhanila; Li, Fan; Yang, Qun; Blake, Graeme R.; Parkin, Stuart; Auffermann, Gudrun; Sun, Yan; Muller, David A.; et al. (ACS Energy Letters, 2019)
The observation of extraordinarily high conductivity in delafossite-type PdCoO2 is of great current interest, and there is some evidence that electrons behave like a fluid when flowing in bulk crystals of PdCoO2. Thus, this material is an ideal platform for the study of the electron transfer processes in heterogeneous reactions. Here, we report the use of bulk single-crystal PdCoO2 as a promising electrocatalyst for hydrogen evolution reactions (HERs). An overpotential of only 31 mV results in a current density of 10 mA cm-2, accompanied by high long-term stability. We have precisely determined that the crystal surface structure is modified after electrochemical activation with the formation of strained Pd nanoclusters in the surface layer. These nanoclusters exhibit reversible hydrogen sorption and desorption, creating more active sites for hydrogen access. The bulk PdCoO2 single crystal with ultrahigh conductivity, which acts as a natural substrate for the Pd nanoclusters, provides a high-speed channel for electron transfer.
CRIS-Team Scopus Importer:2022-04-14